2019
DOI: 10.1086/705478
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Realizability and Biological Modality

Abstract: Critics of multiple realizability have recently argued that we should concentrate solely on actual here-and-now realizations that are found in nature. The possibility of alternative, but unactualized, realizations is regarded as uninteresting because it is taken to be a question of pure logic or an unverifiable scenario of science fiction. However, in the biological context only a contingent set of realizations is actualized. Drawing on recent work on the theory of neutral biological spaces, the article shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The Library of Mendel is basically a logical space consisting of descriptions of genomes, whose standard codes in known living systems consist of only four characters (A, C, G, and T). It is noteworthy that Dennett allows for alternative genetic systems as well, which would lead to other spaces of possibilities (Koskinen 2019).…”
Section: Spaces Of the (Biologically) Possiblementioning
confidence: 99%
See 1 more Smart Citation
“…The Library of Mendel is basically a logical space consisting of descriptions of genomes, whose standard codes in known living systems consist of only four characters (A, C, G, and T). It is noteworthy that Dennett allows for alternative genetic systems as well, which would lead to other spaces of possibilities (Koskinen 2019).…”
Section: Spaces Of the (Biologically) Possiblementioning
confidence: 99%
“…The Library of Mendel is basically a logical space consisting of descriptions of genomes, whose standard codes in known living systems consist of only four characters (A, C, G, and T). It is noteworthy that Dennett allows for alternative genetic systems as well, which would lead to other spaces of possibilities (Koskinen 2019). Evolutionary biologist Andreas Wagner has similarly invoked the metaphor of the library in depicting the spaces of evolutionary explorations (e.g., Wagner 2014).…”
Section: Spaces Of the (Biologically) Possiblementioning
confidence: 99%
“…The rapidly advancing toolkit of biological engineering, and the consequent capabilities on intervening in the living world makes it easier to see possibilities where they earlier remained hidden. In contrast to previous armchair/work desk/dry lab approaches, synthetic biology can experimentally study alternative biological designs that are not found in nature, but which could nevertheless realize familiar biological functions, when concretized (see Koskinen 2019b). Both minimal cells and alternative genetic systems keep some fundamental biological functions fixed, while their naturally evolved material realizers, or at least some important parts of them, are changed.…”
Section: Synthetic Semi-fictions and The Semifactual Strategymentioning
confidence: 99%